MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI PERMAINAN FINGER PAINTING BAGI ANAK TUNAGRAHITA RINGAN - Yunita Handa Yetri (Jurnal Penelitian Pendidikan Khusus, 2014)
This study originated from the problems found mild mental retardation in a child class I in SDLB N 20 Pondok Duo Pariaman who can not recognize the color. This study aims to determine whether through games or finger painting can improve color recognition. This type of research is experimental research in the form of single-subject research (SSR) using ABA design and data analysis techniques using visual analysis chart. Research results yauti Baseline condition (A1) 22:22% -33.33%, intervention (B) 11:11% -88.88%, baseline (A2) 66.66% -88.88%.